(untitled) (Research, Society and Development, 2020)
Among all the pathologies affecting the stomatognathic system, temporomandibular dysfunction (TMD) is quite prevalent in the Brazilian population. The causes of TMD are several, among them the psychosomatic diseases, which can initiate or even intensify a dysfunction already established, including the side effects resulting from the treatment of these psychological changes. This work aimed, through a clinical study, to evaluate the prevalence of psychosomatic diseases, their side effects of treatment and to review the literature their relationship with TMD. This is an observational, cross-sectional study conducted at the Dental Clinics of the University of Paraná - UNIPAR campus Cascavel, from March 2015 to August 2016. The volunteers filled out a questionnaire regarding their systemic condition, harmful habits and hygiene, the data were submitted to descriptive statistics in Excel for Windows software spreadsheets. The results showed that 42.7% had some systemic change, among these, 6.30% were carriers of psychosomatic diseases, depression was the most prevalent (96%) followed by anxiety (4%), while 45% reported having xerostomia. Therefore, the number of carriers of psychosomatic diseases is considerably high, as well as side effects related to treatment, requiring a careful analysis of the patient, because they can cause damage to oral health and also to Temporomandibular Joint.